A water droplet erosion-induced fatigue crack propagation and failure in X20Cr13 martensitic stainless-steel turbines working at low pressure. (September 2022) - Khan, Mohd Sarim; Sasikumar, C.
Graphical abstract: Highlights: Turbine blade failures caused by mixed factors, including corrosion, erosion, and turbine vibrations, followed by fatigue crack growth and failure is reported. In this study, we identified the transformation of chromium carbide precipitates in the martensitic matrix into chrome oxides during steam condensation. Our study examines how steam impingement eroding these chromium oxides changes the surface roughness of turbine blades and how that affects the turbine vibrations. The exhaust side of the steam turbine was subjected to a pressure drop, which caused pitting corrosion, corrosion, and surface roughness on the blades. Although deep pits are created on the leading edges of the blades, it's interesting to note that the fatigue crack propagates from the trailing edge. Abstract: A low-pressure steam turbine blade failed at a thermal power plant reported in this paper. Few blades were damaged on the exhaust side, and the cracks originated on the trailing edge and spread toward the leading edge of blade. In the crack initiation point, shallow corrosion pits were evident, however, turbine vibrations were found to be actuating crack initiation and propagation. Due to numerous pits observed on blades surface, there were vibrations. A pressure drop on the exhaust side of the steam turbine caused condensation and water droplets impinging on the blades caused severe erosion. Upon contact with the condensed water droplets, the chromium carbide precipitates in the martensitic matrix converted into chrome oxides, and impingement of high velocity steam erodes these oxides, causing a rough surface with honeycombed texture. As a result of the roughened blade surfaces, fatigue cracks form at potentially weaker areas and subsequently the final fracture.